Yip1A, a Novel Host Factor for the Activation of the IRE1 Pathway of the Unfolded Protein Response during Brucella Infection - Taguchi, Yuki; Imaoka, Koichi; Kataoka, Michiyo; Uda, Akihiko; Nakatsu, Daiki; Horii-Okazaki, Sakuya; Kunishige, Rina; Kano, Fumi; Murata, Masayuki (PLoS pathogens, 2015)
Brucella species replicate within host cells in the form of endoplasmic reticulum (ER)-derived vacuoles. The mechanisms by which the bacteria are sequestered into such vacuoles and obtain a continuous membrane supply for their replication remain to be elucidated. In the present study, we provided several lines of evidence that demonstrate the mechanism by which B. abortus acquires the ER-derived membrane. First, during Brucella infection, the IRE1 pathway, but not the PERK and ATF6 pathways, of the unfolded protein response (UPR) was activated in a time-dependent manner, and the COPII vesicle components Sar1, Sec23, and Sec24D were upregulated. Second, a marked accretion of ER-derived vacuoles was observed around replicating bacteria using fluorescent microscopy and electron microscopy. Third, we identified a novel host factor, Yip1A, for the activation of the IRE1 pathway in response to both tunicamycin treatment and infection with B. abortus. We found that Yip1A is responsible for the phosphorylation of IRE1 through high-order assembly of Ire1 molecules at ER exit sites (ERES) under the UPR conditions. In Yip1A-knockdown cells, B. abortus failed to generate the ER-derived vacuoles, and remained in endosomal/lysosomal compartments. These results indicate that the activation of the IRE1 pathway and the subsequent formation of ER-derived vacuoles are critical for B. abortus to establish a safe replication niche, and that Yip1A is indispensable for these processes. Furthermore, we showed that the autophagy-related proteins Atg9 and WIPI1, but not DFCP1, were required for the biogenesis of the ER-derived membrane compartments. 　On the basis of our findings, we propose a model for intracellular Brucella replication that exploits the host UPR and ER-derived vacuole formation machineries, both of which depend on Yip1A-mediated IRE1 activation.